Tomatoes for Neela - Lakshmi, Padma; Martinez-Neal, Juana (New York : Viking, 2021)
As Neela and her mother cook together, they find a way for Neela's grandmother, who lives in India, to share in both the love and the flavors of the day. Includes tomato facts.
Includes bibliographical references.
Keywords: Cooking (Tomatoes) -- Juvenile fiction; Tomatoes -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Grandmothers -- Juvenile fiction; East Indian Americans -- Juvenile fiction; Cooking (Tomatoes) -- Fiction; Tomatoes -- Fiction; Mothers and daughters -- Fiction; Grandmothers -- Fiction; East Indian Americans -- Fiction; Picture books